2013
DOI: 10.1103/physrevlett.110.177405
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Control of Light Scattering from Nanostructured Materials by Second-Harmonic Generation

Abstract: We introduce an active, all-optical method for controlling the intensity and directionality of light scattering from single nanostructures. The method is based on the coherent interplay between linear light scattering and second-harmonic generation. The intensity and directionality of scattered light can be controlled by the phase delay and the relative angle between excitation beams. We discuss the principle of this coherent control technique and perform numerical model calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 37 publications
(24 reference statements)
0
45
0
Order By: Relevance
“…The literature suggests that the interference between different second harmonic modes, and thus their relative phase, plays an important role in the observed emission patterns [42,43]. Especially, it was shown that the phase induced by the fundamental dipolar mode allows controlling the forward and backward second harmonic emission [27,42,44]. For this reason, the multipolar analysis is further refined in Fig.…”
mentioning
confidence: 99%
“…The literature suggests that the interference between different second harmonic modes, and thus their relative phase, plays an important role in the observed emission patterns [42,43]. Especially, it was shown that the phase induced by the fundamental dipolar mode allows controlling the forward and backward second harmonic emission [27,42,44]. For this reason, the multipolar analysis is further refined in Fig.…”
mentioning
confidence: 99%
“…SH generation from nanostructured metals has received wide interest in the last few years. The dependence of the SH radiation on the polarization of the pump beam and the particle shape has been addressed for metallic colloids as well as for planar arrays of nanoparticles on a substrate [8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
mentioning
confidence: 99%
“…All-optical coherent control of surface plasmons in single or coupled nanoantennas is of fundamental importance, since they can be viewed as building blocks of plasmonic metamaterials (MMs), metasurfaces and optical components such as sensors, switches, transistors and light sources. Coherent control over the linear [6,10], nonlinear [11] and spatially nonlocal [12] responses of plasmonic nanoantennas has been reported, as well as controlling the directionality of emission, scattering patterns and absorption in nanoparticles (NPs) involving nonlinear processes [13][14][15]. Moreover, coherent control of modal excitations in plasmonic metamolecules are investigated through adjusting the position of an exciting high-energy electron beam over a dolman style resonator [16] or by changing the relative phase of two orthogonally polarized light fields, exciting a triple nanorod structure [17].…”
mentioning
confidence: 99%